An Evaluation of the Impact of Introducing Compassion Focused Therapy to a Standard Treatment Programme for People with Eating Disorders. (28th June 2012) - Gale, Corinne; Gilbert, Paul; Read, Natalie; Goss, Ken
<x xml:space="preserve">Abstract</x> Objective This study explored the outcome of introducing Compassion Focused Therapy (CFT) into a standard treatment programme for people with eating disorders. In particular, the aim was to evaluate the principle that CFT can be used with people with eating disorders and improve eating disorder symptomatology. Method Routinely collected questionnaire data were used to assess cognitive and behavioural aspects of eating disorders and social functioning/well being (n = 99). Results There were significant improvements on all questionnaire measures during the programme. An analysis by diagnosis found that people with bulimia nervosa improved significantly more than people with anorexia nervosa on most of the subscales. Also, in terms of clinical significance, 73% of those with bulimia nervosa were considered to have made clinically reliable and significant improvements at the end of treatment (compared with 21% of people with anorexia nervosa and 30% of people with atypical eating disorders). Conclusion This study demonstrates the potential benefits of using CFT with people with eating disorders and highlights the need for further research on this new approach. Copyright © 2012 John Wiley & Sons, Ltd. Key Practitioner Message CFT offers new ways to conceptualize and formulate some of the self‐critical and shame‐based difficulties associated with eating disorders. CFT offers a framework that can enable people with eating disorders to conceptualize their difficulties in different ways. CFT can be combined with standard therapies especially cognitive behavioural therapy. CFT can be especially useful in a group context where the relationships between members can become increasingly compassionate, validating, supportive and encouraging.